Dietary protection against the visual and motor deficits induced by experimental autoimmune encephalomyelitis - Zyla-Jackson, Katarzyna; Walton, Dorothy A.; Plafker, Kendra S.; Kovats, Susan; Georgescu, Constantin; Brush, Richard S.; Tytanic, Madison; Agbaga, Martin-Paul; Plafker, Scott M. (Frontiers in Neurology, 2023)
Introduction Five to eight percent of the world population currently suffers from at least one autoimmune disorder. Despite multiple immune modulatory therapies for autoimmune demyelinating diseases of the central nervous system, these treatments can be limiting for subsets of patients due to adverse effects and expense. To circumvent these barriers, we investigated a nutritional intervention in mice undergoing experimental autoimmune encephalomyelitis (EAE), a model of autoimmune-mediated demyelination that induces visual and motor pathologies similar to those experienced by people with multiple sclerosis (MS). Methods EAE was induced in female and male mice and the impact of limiting dietary carbohydrates by feeding a ketogenic diet (KD) enriched in medium chain triglycerides (MCTs), alpha-linolenic acid (an omega-3 fatty acid), and fiber was evaluated in both a preventive regimen (prior to immunization with MOG antigen) and an interventional regimen (following the onset of symptoms). Motor scores were assigned daily and visual acuity was measured using optokinetic tracking. Immunohistochemical analyses of optic nerves were done to assess inflammatory infiltrates and myelination status. Fatty acid and cytokine profiling from blood were performed to evaluate systemic inflammatory status. Results The KD was efficacious when fed as a preventive regimen as well as when initiated as an interventional regimen following symptom onset. The KD minimally impacted body weight during the experimental time course, increased circulating ketones, prevented motor and ocular deficits, preserved myelination of the optic nerve, and reduced infiltration of immune cells to optic nerves. The KD also increased anti-inflammatory-associated omega-3 fatty acids in the plasma and reduced select cytokines in the circulation associated with EAE-mediated pathological inflammation. Discussion In light of ongoing clinical trials using dietary strategies to treat people with MS, these findings support that a KD enriched in MCTs, omega-3 fatty acids, and fiber promotes a systemic anti-inflammatory milieu and ameliorates autoimmune-induced demyelinating visual and motor deficits.